Polymer planar Bragg grating sensor for static strain measurements - Rosenberger, Manuel; Koller, G.; Belle, S.; Schmauß, Bernhard; Hellmann, R. (Optics Letters, 2013)
We report on a new optical strain sensor based on a polymer planar Bragg grating (PPBG). The sensor consists of commercially available bulk Polymethlymethacrylate with a UV-inscribed optical waveguide as well as a Bragg grating, both of which are fabricated simultaneously in a single writing step. Upon axial strain, the Bragg wavelength reveals a quasi-instantaneous spectral red shift that depends linearly on the mechanical load with a sensitivity of 2.95 pm/με. The relative reflected intensity of the PPBG remains constant in the investigated load region. © 2013 Optical Society of Americ
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.LEH.polyme